The Effect of MicroRNA-126 Mimic Administration on Vascular Perfusion Recovery in an Animal Model of Hind Limb Ischemia - Theofilis, Panagiotis; Vogiatzi, Georgia; Oikonomou, Evangelos; Gazouli, Maria; Siasos, Gerasimos; Katifelis, Hector; Perrea, Despoina; Vavuranakis, Manolis; Iliopoulos, Dimitrios C; Tsioufis, Costas; Tousoulis, Dimitris (Frontiers in Molecular Biosciences, 2021)
Background: MicroRNAs have been linked to angiogenesis and could prove to be valuable future therapeutic targets in ischemic cardiovascular diseases. Methods: Ten-week-old male C57Bl/6 mice were subjected to left femoral artery ligation and were treated with microRNA-126 mimic at a dose of 5mg/kg (Group A, n=10) or 5mg/kg microRNA mimic negative control (Group B, n=10) on days 1, 3 and 7. Laser Doppler imaging was performed to verify successful ligation on day 0 and to evaluate differences in the ischemic-to-normal (I/N) hind limb perfusion ratio on day 28. Muscle tissue expression of microRNA-126 and vascular endothelial growth factor (VEGF) was determined via PCR. Results: Following microRNA-126 mimic administration in Group A subjects, we noted a stepwise increase in I/N hind limb perfusion ratio (Day 0: 0.364±0.032 vs. Day 8: 0.788±0.049 vs. Day 28: 0.750±0.039, p=0.001). In Group B a stepwise increase in I/N hind limb perfusion ratio was observed (Day 0: 0.272±0.057 vs. Day 8: 0.382±0.020 vs. Day 28: 0.542±0.028, p=0.074). Tissue expression of microRNA-126 in the ischemic hind limb of Group A was 350-fold lower compared to the ischemic hind limb of Group B (p<0.001). A higher expression (14.2-fold) of VEGF in the ischemic hind limb of microRNA-126-treated mice compared to that of control group was detected (p<0.001). A statistically significant negative correlation was noted between microRNA-126 and VEGF tissue expression levels in the ischemic limbs of the entire study population. Conclusion: MicroRNA-126 delivery in the ischemic hind limb of mice improved vascular perfusion recovery with VEGF upregulation.